1988
DOI: 10.1063/1.866823
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a strong-current ion ring on spheromak stability

Abstract: The stability of a spheromak with an energetic ion ring, carrying a current comparable to the plasma current, to the tilt mode is considered. For small departures from sphericity a perturbative approach is applied to an appropriate energy principle in order to calculate the lowest nontrivial kinetic contribution of the ion ring. An analytic stability criterion is obtained. It is seen that the prolate configuration becomes more stable while the oblate one is less stable than in the absence of the ring. The prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…They have also shown that the unstable rings will naturally evolve, through increase in the axial ion temperature, to stable shapes if in the initial formation process they are axially short. It has also been predicted that ion rings could stabilize compact torus configurations [11,12,13,14]. A linearized 3-D hybrid code was constructed for stability studies of field-reversed ion rings [15] but lacked the ability to examine nonlinear ef-FIG.…”
Section: Scalar Resistivity and Macro-particles Experience Slowing-domentioning
confidence: 99%
“…They have also shown that the unstable rings will naturally evolve, through increase in the axial ion temperature, to stable shapes if in the initial formation process they are axially short. It has also been predicted that ion rings could stabilize compact torus configurations [11,12,13,14]. A linearized 3-D hybrid code was constructed for stability studies of field-reversed ion rings [15] but lacked the ability to examine nonlinear ef-FIG.…”
Section: Scalar Resistivity and Macro-particles Experience Slowing-domentioning
confidence: 99%